The Impact of the Roman Army (200 B.C. - A.D. 476): Economic, Social, Political, Religious and Cultural Aspects Proceedings of the Sixth Workshop of the International Network Impact of Empire (Roman Empire, 200 B.C. - A.D. 476), Capri, Italy, March 29-April 2, 2005 - de Blois, Lukas; Lo Cascio, Elio; Hekster, Olivier; de Kleijn, Gerda (Impact of Empire, 2007)
This sixth volume of the network Impact of Empire offers a comprehensive reading on the economic, political, religious and cultural impact of Roman military forces on the regions that were dominated by the Roman Empire. Readership: All those interested in the history of the Roman Empire and the impact of its military forces, and military history in general, particularly classicists, ancient historians, archaeologists, and specialists in Roman law.